(untitled) (Marketing Journal, 2025)
The concept of welfare has long been regarded as the ultimate goal of every nation and as a key indicator of a countryʼs development. Enhancing public welfare is highlighted as one of the most important criteria for evaluating the effectiveness of state so cio-economic policy. The decisions currently being implemented in our country serve as clear evidence of this. The paper discusses the idea that improving public welfare constitutes the principal objective of social development. In this regard, various terms such as “standard of living,” “public welfare,” and other related notions have been employed to express the level of well -being of the population. The study also considers the extent to which the material, spiritual, and social needs of the population 85 are being met in Uzbekistan, and presents forward -looking perspectives, reflections, and proposals.